Review of Selected Bio-Wastes as Potential Materials for Alkali-Activation for Cement-Based Products - K. A. Olonade; H. Mohammed (Nigerian Journal of Technological Development, 2019)
There is growing need to finding alternative binder for Ordinary Portland Cement (OPC) as a result of the environmental hazards associated with its production. This paper presents the result of the review of selected bio-wastes as potential materials for alkali-activation in cement-based products. Studies carried out by several authors on the use of ashes from rice husk, cassava peel, sugarcane straw, corn cob and coconut shells were critically reviewed, while their chemical compositions as well as other criteria for alkali activation were identified. The review showed that the combined composition of SiO2, Al2O 3 and Fe2O3 were in the ranges of 67.90 – 93.60, 46.59 – 72.25, 73.79 – 83.02, 41.13 – 78.30 and 71.3 – 77.57 % for rice husk ash, cassava peel ash, sugarcane straw ash, corn cob ash and coconut shell ash, respectively. These values met the requirement of ASTM 618 for materials to be considered as pozzolan, while the hydraulic coefficients of the ashes were also found comparable to notable industrial wastes that have been utilized for alkali-activation. It was also found that these materials are still not explored for alkali-activation. The paper concluded that the ash from these materials could be alkali activated to produce binders in cement-based products due to their potential properties.